Determining active sensor nodes for complete coverage without location information. (18th November 2005) - Wu, Tzu-Ting; Ssu, Kuo-Feng
Selecting a partial set of sensor nodes for maintaining full system sensing coverage is an important issue in wireless sensor networks. Previous research was concentrated on the location-aware sensor environments; little attention has been devoted to the location-free networks that are more difficult to detect blind spots. This paper describes an approach to determining active nodes for complete coverage without their location information. A triangular self-test mechanism is designed to examine the existence of blind areas and to activate appropriate sensor nodes for covering the areas. The selection mechanism was developed and evaluated using network simulator ns-2. Two related algorithms, PEAS and OGDC, were also implemented for performance comparison. The simulation measured the metrics in control overhead, size of the active set, and sensing coverage. The results show that our algorithm aids profit in network scalability, energy efficiency, and number of active sensor nodes in the location-free wireless sensor network.